Negative polarization of light at backscattering from a numerical analog of planetary regoliths - Grynko, Yevgen; Shkuratov, Yuriy; Alhaddad, Samer; Förstner, Jens (Icarus)
We model negative polarization, which is observed for planetary regoliths at backscattering, solving a full wave problem of light scattering with a numerically exact Discontinuous Galerkin Time Domain (DGTD) method. Pieces of layers with the bulk packing density of particles close to 0.5 are used. The model particles are highly absorbing and have irregular shapes and sizes larger than the wavelength of light. This represents a realistic analog of low-albedo planetary regoliths. Our simulations confirm coherent backscattering mechanism of the origin of negative polarization. We show that angular profiles of polarization are stabilized if the number of particles in a layer piece becomes larger than ten. This allows application of our approach to the negative polarization modeling for planetary regoliths.
Keywords: tet_topic_scattering

In-Mold-Assembly of Hybrid Bending Structures by Compression Molding - Stallmeister, Tim; Tröster, Thomas (Key Engineering Materials)
The further development of in-mold-assembly (IMA) technologies for structural hybrid components is of great importance for increasing the economic efficiency and thus the application potential. This paper presents an innovative IMA process concept for the manufacturing of bending loaded hybrid components consisting of two outer metal belts and an inner core structure made of glass mat reinforced thermoplastic (GMT). In this process, the core structure, which is provided with stiffening ribs and functional elements, is formed and joined to two metal belts in one single step. For experimental validation of the concept, the development of a prototypic molding tool and the manufacturing of hybrid beams including process parameters are described. Three-point bending tests and optical measurement technologies are used to characterize the failure behavior and mechanical properties of the produced hybrid beams. It was found that the innovative IMA process enables the manufacturing of hybrid components with high energy absorption and low weight in one step. The mass-specific energy absorption is increased by 693 % compared to pure GMT beams.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Combined Ranking and Regression Trees for Algorithm Selection - Fehring, Lukas

Multi-Objective Trust-Region Filter Method for Nonlinear Constraints using Inexact Gradients - Berkemeier, Manuel Bastian; Peitz, Sebastian (arXiv:2208.12094)
In this article, we build on previous work to present an optimization algorithm for nonlinearly constrained multi-objective optimization problems. The algorithm combines a surrogate-assisted derivative-free trust-region approach with the filter method known from single-objective optimization. Instead of the true objective and constraint functions, so-called fully linear models are employed and we show how to deal with the gradient inexactness in the composite step setting, adapted from single-objective optimization as well. Under standard assumptions, we prove convergence of a subset of iterates to a quasi-stationary point and if constraint qualifications hold, then the limit point is also a KKT-point of the multi-objective problem.

Einbettung von Augmented Reality in den Experimentierprozess - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Unsicherheit als Element von naturwissenschaftsbezogenen Bildungsprozessen)
Keywords: augmented reality; modelle; digitale Medien

Moodle in der Hochschullehre: Struktur durch HTML-Code - Fiege, Amanda Sophie; Pape, Stefan (#MoodleKannMehr – nicht nur im Distanzunterricht!)

Authentic Englishes.nrw – Developing and Using Interactive Teaching and Learning Materials on Varieties of English - Pape, Stefan; Fiege, Amanda Sophie; Mindt, Ilka (Selected Papers from the 2021 Conference of the German Association for the Study of English)

Kollaborative Autoethnographien digitaler Praktiken. Eine konzeptionelle, methodische und theoretische Einführung zu einem Lehr-Forschungsprojekt im ersten Corona-Semester - Steinhardt, Isabel (DNGPS Working Paper)
Keywords: Open Science; kollaborative Autoethnographie

MapOSR - A mapping review dataset of empirical studies on Open Science - Lasser, Jana; Schneider, Jürgen; Lösch, Thomas; Röwert, Ronny; Heck, Tamara; Bluemel, Clemens; Neufend, Maike; Steinhardt, Isabel; Skupien, Stefan (F1000Research)
<ns3:p>Research that investigates respective researchers’ engagement in Open Science varies widely in the topics addressed, methods employed, and disciplines investigated, which makes it difficult to integrate and compare its results. To investigate current outcomes of Open Science research, and to get a better understanding on well-researched topics and research gaps, we aimed at providing an openly accessible overview of empirical studies that focus on different aspects of Open Science in different scientific disciplines, academic groups and geographical regions. In this paper, we describe a data set of studies about Open Science practices retrieved following a PRISMA approach to compile a literature review. We included studies from the Scopus and Web of Science databases with keywords relating to Open Science between the years 2000 and 2020, as well as a snowball search for relevant articles. Studies that did not investigate any aspect of Open Science, or weren’t peer-reviewed were excluded, resulting in a total of 695 remaining studies.<ns3:italic> </ns3:italic>The data set was collaboratively annotated to ensure intercoder reliability of the coded data.</ns3:p>
Keywords: Open Science

Qualitative und quantitative Inhaltsanalyse: digital und automatisiert. Eine anwendungsorientierte Einführung mit empirischen Beispielen und Softwareanwendungen - Schneijderberg, Christian; Wieczorek, Oliver; Steinhardt, Isabel
Zur Inhaltsanalyse gibt es bereits diverse Methodenbücher. Warum sollten Sie also genau das vorliegende Methodenbuch „Qualitative und quantitative Inhaltsanalyse: digital und automatisiert “lesen? Erstens schließt dieses Buch eine Lücke, der wir in der Lehre und bei Methodenworkshops immer wieder begegnet sind. Diese Lücke besteht darin, dass selten eine Übersicht über und Gegenüberstellung verschiedener Methoden der qualitativen und quantitativen Inhaltsanalyse gegeben wird. Zudem haben bisherige Lehr-und Methodenbücher in den Sozialwissenschaften teil-und vollautomatisierte Verfahren der Textanalyse noch nicht aufgegriffen und diese mit bereits etablierten Verfahren qualitativer und quantitativer Inhaltsanalyse verknüpft. Zweitens bietet dieses Buch im ersten Teil eine systematische und anwendungsorientierte Einführung zu den Grundlagen inhaltsanalytischer empirischer Sozialforschung. Im zweiten Teil werden detaillierte Anleitungen von digital unterstützten qualitativen inhaltsanalytischen Auswertungstechniken gegeben. Den teil-und vollautomatisierten quantitativen inhaltsanalytischen Auswertungstechniken widmet sich der dritte Teil des Buches. Bei digital unterstützten Verfahren werden Sie durch Software bei Ihrer Analyse unterstützt, beispielsweise bei der digitalen Organisation Ihrer Daten und bei der digitalen Durchführung der Auswertung. Bei teilautomatisierten Verfahren der Inhaltsanalyse nehmen Ihnen Software und Tools Teile der Datenanalyse ab, wohingegen bei vollautomatisierten Verfahren der gesamte Auswertungsprozess und oftmals auch die Datenbeschaffung durch Programme und Tools durchgeführt wird.
Keywords: qualitative Inhaltsanalyse; quantitative Inhaltsanalyse